Oxford international primary English Student book 3 - Barber, Alison (Oxford Oxford university press, 2021)
The *Oxford International English Student Book 3* is a comprehensive resource designed to develop key English language skills for primary-level students. It combines engaging texts, structured activities, and stimulating illustrations to enhance reading, writing, listening, and speaking abilities. With a focus on fostering critical thinking and creativity, the book introduces a variety of themes and genres, encouraging global awareness and cultural appreciation. Aligned with international educational standards, it supports a progressive learning journey, ensuring students build a strong foundation in English.